Assessment on In Vitro Probiotic Attributes of Lactobacillus plantarum Isolated From Horse Feces. - Khusro, Ameer; Rivas Caceres, Raymundo Rene; Valan Arasu, Mariadhas; Khayam Sahibzada, Muhammad Umar; Salem, Abdelfattah Z.M; Abdullah Al-Dhab, Naif; Seidelf, Veronique; Choi, Ki Choon (2021)
This study was designed to assess in vitro probiotic attributes of potent bacterium isolated from the feces of healthy horse. Initially, a total of eight bacteria were isolated from the feces and evaluated their an tibacterial activities against indicator bacterial pathogens using agar well diffusion assay. Results showed significant (P < .05) antibacterial property of Lactobacillus plantarum strain LF4 against pathogens tested with maximum growth inhibitory activity of 320.16 ± 3.4 AU/mL against Staphylococcus aureus. Further, in vitro probiotic properties of strain LF4 were determined using standard methodologies. Strain LF4 main tained its viability towards acidic condition (pH 2.0) and simulated gastric juice (pH 2.0) with total cell counts of 1.6 ± 0.18 and 1.7 ± 0.18 log cfu/mL, respectively. Moreover, the strain was observed resistant to oxgall (0.5% w/v) up to 36 hours. The isolate showed significant (P < .05) hydrophobicity property (60.3 ± 1.6%), auto-aggregation trait (41.31 ± 1.5%), and moderate proteolytic activity. Strain LF4 revealed significant (P < .05) rate of DPPH scavenging (15.3 ± 1.3-69.7 ± 1.3%) and hydroxyl radical scavenging (11.3 ± 1.3 to 56.4 ± 1.3%) in a concentration dependent manner. Additionally, the isolate was observed susceptible to all the conventional antibiotics tested, thereby indicating its safer utilization. In conclusion, findings suggested the colossal applications of L. plantarum strain LF4 as an ideal probiotic bacterium in equine industries.